PENERAPAN MULTIPLE INTELLIGENCE DALAM PEMBELAJARAN MATEMATIKA: ANALISIS PADA KECERDASAN MUSIK - Suwanto Suwanto; Ade Evi Fatimah; Fitriani Fitriani (Mahesa Research Center, 2020)
Less optimal musical intelligence in students and improper application in mathematics learning is the basis for the preparation of articles. The misunderstanding of applying musical intelligence is quite alarming, for example when students learn to listen to music, they actually don't use their musical intelligence to learn or change their behavior. In this condition, music has a role in arousing motivation, memory and reflexes to learn, not using musical intelligence to learn. The preparation of this article uses the literature review method with the keywords musical intelligence (musical intelligence), learning and learning mathematics in books and journals indexed by Googles choolar. The application of musical intelligence in mathematics learning requires careful consideration and expertise in designing learning to be carried out. Some examples of using musical intelligence in learning mathematics include converting notes into numbers, solving math problems related to scales, designing memorization of mathematical formulas in the form of chants that are fun for students.